2008
DOI: 10.1007/s11096-008-9240-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse-drug-reaction related admissions to a hospital in Scotland

Abstract: The proportion of ADR-related admissions was lower than in previous studies in the UK. A substantial proportion of ADRs was associated with NPMs, highlighting the need for greater awareness amongst patients, prescribers and other health care professionals regarding possible serious adverse effects caused by these medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
5
31
2
Order By: Relevance
“…The studies were conducted between 1992 and 2006. The study periods ranged from two weeks [35] to 21 months [36]. Fourteen studies had a prospective design [23]-[26], [28]-[36], [38], one retrospective [37], and one cross-sectional [27].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted between 1992 and 2006. The study periods ranged from two weeks [35] to 21 months [36]. Fourteen studies had a prospective design [23]-[26], [28]-[36], [38], one retrospective [37], and one cross-sectional [27].…”
Section: Resultsmentioning
confidence: 99%
“…31 Several other studies have reported similar findings with 60-70% of ADRs being classes as preventable. 4,32,33,34 …”
Section: Preventabilitymentioning
confidence: 99%
“…For example, using medical record review, ADRs and adherence problems [4-6] and ADRs exclusively [7,8] have been shown to contribute to 2.7-8.0% of admissions to UK hospitals [4-8]. These figures are comparable to a recent international systematic review [9] which concluded that 5.8% of admissions are caused by ADRs.…”
Section: Introductionmentioning
confidence: 84%